2003
DOI: 10.1164/rccm.200205-479oc
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Activation of Nuclear Factor–κB Signaling Pathway in Severe Uncontrolled Asthma

Abstract: The transcription factor nuclear factor-kappaB (NF-kappaB) is inactive when bound to its inhibitory protein IkappaBalpha. On cell stimulation with inflammatory signals, IkappaBalpha is phosphorylated by IkappaB kinases and subsequently degraded. Freed NF-kappaB then induces expression of cytokines such as granulocyte-macrophage colony-stimulating factor, interleukin-8, and regulated upon activation, normal T cell expressed and secreted. These mediators are overexpressed in asthma and are downregulated by gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
128
0
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(135 citation statements)
references
References 45 publications
2
128
0
5
Order By: Relevance
“…1,2,8 In addition to the evidence of enhanced NF-kB activity in peripheral blood mononuclear cells of asthmatic patients, 9 our previous studies also demonstrated that NF-kB signal transduction, p38 MAPK and extracellular signal-regulated kinase (ERK) pathways played pivotal roles in regulating IL-3, IL-5 and granulocyte macrophage colonystimulating factor-induced intercellular adhesion molecule (ICAM)-1 expression and Th17 cytokine-elicited cytokine production from human eosinophils. 10,11 In an attempt to further investigate the activation of eosinophils induced by IL-33, we elucidated the intracellular signaling mechanisms regulating the survival, adhesion, and cytokine and chemokine release from eosinophils activated by IL-33, and we compared the effects of two other structurally and functionally related IL-1 family cytokines, IL-1b and IL-18.…”
Section: Introductionmentioning
confidence: 75%
“…1,2,8 In addition to the evidence of enhanced NF-kB activity in peripheral blood mononuclear cells of asthmatic patients, 9 our previous studies also demonstrated that NF-kB signal transduction, p38 MAPK and extracellular signal-regulated kinase (ERK) pathways played pivotal roles in regulating IL-3, IL-5 and granulocyte macrophage colonystimulating factor-induced intercellular adhesion molecule (ICAM)-1 expression and Th17 cytokine-elicited cytokine production from human eosinophils. 10,11 In an attempt to further investigate the activation of eosinophils induced by IL-33, we elucidated the intracellular signaling mechanisms regulating the survival, adhesion, and cytokine and chemokine release from eosinophils activated by IL-33, and we compared the effects of two other structurally and functionally related IL-1 family cytokines, IL-1b and IL-18.…”
Section: Introductionmentioning
confidence: 75%
“…PBTs were cultured with pyrrolidinedithiocarbamic acid (PDTC; 500 mM, 24 hours; Sigma), an inhibitor of NF-kB, to evaluate the role of NF-kB. 12 To evaluate pIkBa and GR nuclear translocation, PBTs were cultured (37°C, 5% CO 2 ) with FP, salmeterol, or both for 30 minutes.…”
Section: Pbt Culturesmentioning
confidence: 99%
“…12,19 The cytoplasmic and nuclear protein fractions were separated by using a commercial kit (Pierce, Rockford, Ill) to study GR nuclear translocation. Fifty micrograms of total protein was subjected to SDS-PAGE on 4% to 12% gradient gels (Novex, San Diego, Calif), blotted onto nitrocellulose membranes, blocked with PBS containing 3% BSA and 0.1% Tween 20, and then probed with a polyclonal antibody directed against human procaspases 3 and 8 (Pharmingen and Becton Dickinson), with a polyclonal antibody directed against human GRa (Santa Cruz Biotechnology, Santa Cruz, Calif) or with a polyclonal antibody recognizing pIkBa (Santa Cruz Biotechnology).…”
Section: Pbt Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrophoretic mobility-shift assays and immunohistochemical studies also suggest a greater activation of RelA-containing NF-B dimers in severe asthmatics (17). In mouse models of asthma, mice deficient in either the p50 (13,14) or the c-Rel (15) NF-B subunits, or mice treated with inhibitors of epithelial NF-B activity (18), have significantly reduced levels of eosinophilic lung inflammation when challenged with inhaled allergen.…”
mentioning
confidence: 98%